2013
DOI: 10.1111/jar.12067
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities of Adults with Intellectual Disabilities: What Do We Know? What Do We Do?

Abstract: Background Recent attention to health of people with intellectual disabilities has used a health disparities framework. Building on historical context, the paper summarizes what is known about health disparities from reports and research and provide direction on what to do to reduce these disparities among adults with intellectual disabilities. Methods The present authors examined literature from 2002 to 2011 on health disparities and people with disabilities looking for broad themes on documenting dispariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
191
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(196 citation statements)
references
References 79 publications
4
191
0
1
Order By: Relevance
“…27 Further details on the methods used to identify T2DM and IGR for this programme of research are provided in Chapter 5 (see Outcomes) and Chronic conditions are becoming increasingly important for people with ID as their life expectancy increases. 34 There are a number of risk factors for T2DM that are known to be highly prevalent in people with ID, suggesting that T2DM and CVD may be more prevalent in this group. These risk factors include:…”
Section: Type 2 Diabetes and Impaired Glucose Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Further details on the methods used to identify T2DM and IGR for this programme of research are provided in Chapter 5 (see Outcomes) and Chronic conditions are becoming increasingly important for people with ID as their life expectancy increases. 34 There are a number of risk factors for T2DM that are known to be highly prevalent in people with ID, suggesting that T2DM and CVD may be more prevalent in this group. These risk factors include:…”
Section: Type 2 Diabetes and Impaired Glucose Regulationmentioning
confidence: 99%
“…l sedentary behaviour [35][36][37][38] l a high prevalence of obesity [32][33][34]39 l increased antipsychotic drug use for the management of challenging behaviour 40,41 and psychosis, 42 which are associated with weight gain, hyperglycaemia and worsening of other metabolic CVD risk factors [43][44][45] l genetic conditions associated with obesity (e.g. Prader-Willi syndrome).…”
Section: Type 2 Diabetes and Impaired Glucose Regulationmentioning
confidence: 99%
“…3 Adults with intellectual disabilities are a particularly vulnerable and, from a health perspective, neglected group in society, experiencing considerable health inequalities relative to the general population. 4 Studies have shown that adults with intellectual disabilities have low levels of physical activity 5 and poor nutritional habits, 6 leading to a high prevalence of obesity and diabetes. 7 This evidence suggests that increasing physical activity and reducing sedentary time are priorities for reducing health inequalities in this group.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] Las prioridades a la hora de mejorar la salud de las personas con TDI se deben basar en el diagnóstico temprano, en reducir el impacto de las enfermedades asociadas o comórbidas a la discapacidad, a empoderar a los cuidadores y a la familia, y a la promoción de comportamientos saludables. 13,14 Además, se debe garantizar el acceso equitativo de este colectivo a cualquier proceso diagnóstico y terapéutico en igualdad de condiciones que el resto de la población, situación puesta en entredicho en algunos estudios. 6 De hecho, algunos autores proponen que la deficiencia en su atención sanitaria es una de las causas principales de muertes evitables en esta población.…”
Section: Morbilidad Hospitalaria En Los Trastornos Del Desarrollo Intunclassified